2017
DOI: 10.26719/2017.23.10.662
|View full text |Cite
|
Sign up to set email alerts
|

Factors associated with folic acid knowledge and intake among pregnant women in Sudan

Abstract: Facteurs associés aux connaissances et déterminants concernant l'apport en acide folique parmi les femmes en âge de procréer au SoudanRÉSUMÉ La consommation d'acide folique avant la conception est connue pour avoir un effet protecteur contre les anomalies du tube neural (ATD). La présente étude avait pour objectif d'évaluer les connaissances et déterminants de la sensibilisation à la consommation d'acide folique parmi les femmes enceintes à la maternité de l'hôpital d'Omdourman au Soudan en 2014. Un questionna… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

9
20
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(30 citation statements)
references
References 15 publications
9
20
0
1
Order By: Relevance
“…Women who had at least one or/and more ANC visits presented with good knowledge scores on PCC. Our findings were similar to those conducted in Sudan [ 62 ], and Nigeria [ 63 ]. One potential rationale might be due to ANC visits.…”
Section: Discussionsupporting
confidence: 92%
“…Women who had at least one or/and more ANC visits presented with good knowledge scores on PCC. Our findings were similar to those conducted in Sudan [ 62 ], and Nigeria [ 63 ]. One potential rationale might be due to ANC visits.…”
Section: Discussionsupporting
confidence: 92%
“…Women who were on ANC follow up were nearly two times more likely to have good awareness of NCDs screening during the preconception period than their counterparts. This finding was similar to studies done in Nigeria, Sudan, and Hawassa city, South Ethiopia [ 53 , 55 , 56 ]. This might be due to the reason that women on ANC follow-up might have a greater chance of getting information about preconception care, as health care providers may ask them about their health status before conception and provide counseling on the current and future pregnancies.…”
Section: Discussionsupporting
confidence: 92%
“…This was slightly better than the findings of a study conducted in Pakistan, in which only 18.4% of the participants knew of the importance of folic acid for the unborn foetus [28]. A study conducted in Sudan found that only 8.9% of 1000 pregnant women knew that folic acid prevented birth defects [25].…”
Section: Discussionmentioning
confidence: 72%
“…Anaemia is associated with adverse events in pregnancy and is common among pregnant adolescents. [25]. The participants in the current study demonstrated poor knowledge of the signs and symptoms of anaemia.…”
Section: Discussionmentioning
confidence: 75%